Directional Solidification Experiments with the Transparent Model Alloy Neopentyl Glycol-35wt.%(D)Camphor - Hughes, Turlough Owen (Trinity College Dublin. School of Engineering. Discipline of Mechanical & Manuf. Eng, 2021)
This thesis describes the development of an experimental facility in combination with image processing and computer vision techniques for the visualisation and characterisation of dendritic growth structures in the transparent model alloy Neopentyl Glycol-35wt.%(D)Camphor. The facility enables the control of the mushy zone growth rate and the imposed temperature gradient during solidification and provides in-situ optical video data of the solidification process. A suite of image processing and computer-vision techniques facilitate quantitative data extraction from the in-situ video data. The first is a front-tracking technique for automated tracking of the solidification front position and growth rates during directional solidification. The technique is validated against manual measurement and compared with the traditional liquidus isotherm speed measurement technique, which is widely used for estimating growth rates in directional solidification. Next, the development of a computer vision algorithm for multiple dendrite tip tracking is described. In combination with a thermally calibrated experimental facility, the tracker provides tip velocity and undercooling data for comparison with similar data obtained in microgravity. The data are compared to the traditional LGK model and a modified LGK model adapted with a finite diffusional boundary layer theory to account for convection effects. Finally, mechanisms of competitive growth are investigated in the <111> transparent alloy. Multiple scenarios that obey and disobey the classical Walton-Chalmers rule are described and provide the first examples of competitive crystal growth with associated tip velocity vectors in directionally solidified <111> crystals.
APPROVED
Keywords: Crystal growth; Directional solidification; In-situ; Microstructure formation; Image analysis